Novel or normal? Electric vehicles and the dialectic transition of Nordic automobility - Kester, J; Sovacool, BK; Zarazua de Rubens, G; Noel, L (Elsevier, 2020)
Over the last decade or more, the automobility literature has sought to observe and affect the dynamic tenacity of passenger vehicles. This paper takes up a recent call to actually study how private electric vehicles (EVs) are changing automobility. For this, it identifies four qualitative categories of automobility: general vehicle use, the car in daily life, vehicle symbolism and the effects of electrification. We study how these categories are affected by electric vehicles based on original data we gathered during a large empirical research project in the five Nordic countries, consisting of 227 expert interviews, 8 focus groups and 4322 randomized survey respondents. We find a paradoxical relationship between EVs and automobility. Some aspects embed and strengthen car-based mobility and the current automobility regime, as EVs essentially offer a substitution technology. In other contexts, however, EVs challenge, threaten, and open up questions about automobility and germinate an awareness that it cannot continue as is. We conclude by arguing that the moment transport policy acknowledges this dualism and smartly links up to other developments in transport, like automation and connectivity, policy efforts can be designed to minimize drawbacks and emphasize strengths.